The isolation and identification of antimicrobial peptides and analysis of immune response in E. intermedius embryonic cell line upon exposure to pathogens - Mnisi, Ntando Ghwenneth (My University, 2014)
Insects are confronted by a large variety of potentially harmful microorganisms to which they are resistant as they are able to build up an efficient innate defense system that relies on three tightly interconnected reactions. One of the reactions is the transient and rapid synthesis of a battery of antimicrobial peptides (AMPs). Development of antimicrobial therapeutic drugs and vaccines is very crucial due to factors such as the emergence of multiple-drug resistance. AMPs have been termed natural antibiotics because of their large spectrum of activity. The current study focused on the isolation and identification of cationic antimicrobial peptides and the analysis of immune response in the South African Euoniticellus intermedius embryonic (SAEIE08) cell line upon exposure to pathogens. E. intermedius is of the Coleopteran order in the Scarabaeoidea superfamily. Liquid growth inhibition assay showed higher antimicrobial activity in SAEIE08 that was treated with heat-killed E. coli compared to untreated. Further evidence for antimicrobial activity was seen as a clear zone of inhibition in solid growth inhibition assay when a gel run with protein extracts was plated and overlayed with live E. coli. Changes in protein expression patterns that were analysed in SDS-PAGE and 2-D PAGE indicated the most intense bands and spots at low molecular weight sizes around 10 kDa and/or 16 kDa which implicated increased induction of AMP expression upon exposure to pathogen. Homologues of Saccharomyces cerevisiae proteins were found in some of the 5′/3′ RACE sequences. Possible explanation for matches to these homologues could be that short sequences were used for database searches. The proteins were identified as flavin-containing monooxygenase, long-chain fatty acyl-CoA synthetase, severe depolymerization of actin protein and serine/threonine protein kinase. Interestingly, these proteins play roles in metabolism, cell proliferation and/or molecular pathways which do occur when cells are exposed to stress. There was also an insect peptide allatotropin from Spodoptera frugiperda. The results show that there is inducible antimicrobial activity in embryonic E. intermedius cell line.
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science. Johannesburg, 2014.
Keywords: Peptide antibiotics.; Immune response.; Cell line.; Embryos--Physiology.